Features of Diglossic Stability in Arabic with Counterexamples - Mark Shockley dan Agung Nurcholis (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2016)
Arabic as a macro language is the epitome of classical diglossia as well as the most wellknown and well documented example. Spoken and written Arabic have diverged for so long that some scholars have argued the possibility that Arabic diglossia predates Islam. Regardless of its beginning, numerous cultural and social motivators have held Classical Arabic and Modern Standard Arabic in play as the dialects of prestige. But the prior motivator of this linguistic conservatism for centuries has been the religio-linguistic ideology of Islam. In this paper I analyze sociolinguistic conditions and ideological factors contributing to the stability of Arabic diglossia alongside various counterexamples of diglossic shift.